A New Intraoperative Real-time Monitoring System for Reconstructive Middle Ear Surgery: An Experimental and Clinical Feasibility Study. Issue 10 (December 2016) - Zahnert, Thomas; Metasch, Marie-Luise; Seidler, Hannes; Bornitz, Matthias; Lasurashvili, Nicoloz; Neudert, Marcus
Abstract : Hypothesis: Electromagnetical excitation of ossicular vibration is suitable for middle ear transmission measurements in the experimental and clinical setting. Thereby, it can be used as a real-time monitoring system for quality control in ossiculoplasty. Background: Positioning and coupling of middle ear prosthesis are a precondition for good postoperative hearing results, but at the same time completely dependent upon the surgeon's subjective judgment during surgery. We evaluated an electromagnetically driven measurement system that enables for in vitro and in vivo transmission measurements and thus can be used as a real-time monitoring tool in ossicular reconstruction. Methods: For electromagnetical excitation a magnet was placed on the umbo of the malleus handle and driven by a magnetic field. The induced stapes displacement was picked up by laser Doppler vibrometry on the footplate. Measurements were performed on the intact ossicular chain in five cadaveric temporal bones and during five cochlear implant surgeries. Additionally, two ossiculoplasties were performed under real-time transmission feedback with the monitoring system. Results: Experimentally, the equivalent sound pressure level of the electromagnetic excitation was about 70 to 80 dB which is 10 to 20 dB less than the acoustic stimulation. In the intraoperative setup the generated stapes displacements were about 5 to 20 dB smaller compared with the temporal bone experiments. Applied as real-time feedback system, an improvement in the middle ear transfer function of 4.5 dB in total and 20 dB in partial ossicular reconstruction were achieved. Conclusion: The electromagnetical excitation and measurement system is comparable to the gold standard with acoustical stimulation in both, the experimental setup in temporal bones as well as in vivo. The technical feasibility of the electromagnetical excitation method has been proven and it is shown that it can be used as a real-time monitoring system for ossiculoplasty in the operation room.